O conhecimento da guarda municipal de Curitiba a respeito dos surdos e da língua brasileira de sinais (LIBRAS) - Pereira, Adriano de Souza (2017)
This dissertation discusses the knowledge of the Municipal Guard of a city located in the south of Brazil about deafness and sign language, due to the incipient number of publications that evidence this theme. We turn to the discussion about public policies to encourage accessibility, disabled people´s rights, and deaf people´s right to use sign language in public spaces. This work aims to investigate Members of the Municipal Guard´s knowledge about deaf people and Brazilian Sign Language (LIBRAS), as well as to examine the s rving public servant´s practices when they are faced with situations under which they need to interact with a deaf citizen. As a research methodology, a semi-structured questionnaire was used, which was answered by 50 (fifty) police of the Municipal Guard of the city, who accepted to participate. The calculated data were tabulated and analyzed in their content, through quantitative percentages and axes of qualitative analysis, based on the Content Analysis proposed by Bardin. The results of the research demonstrate that participants working in the Municipal Guard have some knowledge of deafness and limited sign language, from a common sense´s view. At the end of this study, it is understood that the issues surrounding the accessibility process, as well as the Brazilian Sign Language itself (LIBRAS) are fundamental not only for the deaf population but also for society as a whole. In addition, it is suggested that the accessibility´s process must be included in the training programs for these professionals, taking into account human diversity in various instances: social, linguistic, cultural, etc., including the learning of LIBRAS, so that the Server of the Municipal Guard should be qualified to have minimum conditionsto serve the entire population, including the deaf, in their differences and singularities.